ISLAMIC CAPITAL MARKETS : A Comparative Approach - Obiyathulla Ismath Bacha, author 411504; Abbas Mirakhor author 524458 (Singapore ; Hackensack, NJ : World Scientific Publishing Co. Pte. Ltd., 2019)
Islamic Capital Markets: A Comparative Approach (2nd Edition) looks at the similarities and differences between Islamic capital markets and conventional capital markets. The book explains each topic from both the conventional and the Islamic perspective, offering a full understanding of Islamic capital markets, processes, and instruments. In addition to a full explanation of Islamic products, the book also ensures a holistic understanding of the dual markets within which Islamic capital markets operate. Ideal for both students and current practitioners, the second edition of the highly successful Islamic Capital Markets: A Comparative Approach fills a large gap in the current literature on the subject, featuring case studies from Malaysia, Indonesia, Europe, and the Middle East. One of the few comprehensive, dedicated guides to the subject available, the book offers comprehensive and in-depth insights on the topic of Islamic finance for students and professionals alike.